Human Geographies Within the Pale of Settlement Order and Disorder During the Eighteenth and Nineteenth Centuries - Mitchell, Robert E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This study suggests how traditional language-rich narrative histories of the Pale of Settlement can benefit from drawing on the large vocabularies, questions, theories and analytical methods of human geography, economics and the social sciences for an understanding of how Jewish communities responded to multiple disruptions during the nineteenth century. Moving from the ecological level of systems of settlements and variations among individual ones down to the immediate built environment, the book explores how both physical and human space influenced responses to everyday lives and emigration to America. .
1. Orientation, Overview and Omissions -- 2. The Physical Geography of the Pale -- 3. The Human Geography of the Pale -- 4. Individual Settlements are Members of Discrete Settlement Systems -- 5. Ordered Life in Individual Shtetlach, Towns and Cities -- 6. Ordered Life in the Immediate Built and Social Environments -- 7. The Changing Order in the World of Work -- 8. Order and Disorder in Jewish Marriages, Families and Kinship -- 9. Nineteenth-Century Disorder in the Pale and Elsewhere -- 10. A Research Agenda for New Historians.
Keywords: Human geography; Sociology, Urban; Emigration and immigration; Human Geography; Urban Sociology; Human Migration